Health Education About Tepid Water Sponge Efforts to Increase Family Knowledge and Skills in Handling Fever - Rama Nanda; Isna Hikmawati (Proceedings Series on Health & Medical Sciences, 2022)
Fever is a condition of an increase in body temperature above normal. Parents, especially mothers, have an important role in dealing with children with fever, however, not many mothers have the knowledge and skills in early handling of fever, one of which is the tepid water sponge. The purpose of this study is to provide health education about handling fever using the tepid water sponge method.This research with pre-experimental design (one group pretest-posttest). The sample in this study amounted to 30 mothers who have children aged 1-5 years and registered at the Posyandu Bantarkawung Village. Bumiayu District, Brebes Regency. Samples were taken by total sampling technique. Collecting data using a questionnaire sheet for the level of knowledge and observation sheets for skills. Data analysis using paired sample t test. The results showed that the skills before health education were 28 (93.3%) lacking in skills and decreased to 14 people (46.7%) after the intervention. The level of lack of knowledge was 14 (46.7%) and decreased to 5 (16.7%) after the health education intervention. There is a relationship between health education about the tepid water sponge on knowledge and skills in handling fever in the family (p value 0.000). Good public understanding is needed, how to deal with fever in the family through health education.